WIC: Is the United States investing in Breastfeeding or Agriculture?. Issue 2 (March 2021) - Spatz, Diane L.
Abstract : The Special Supplemental Nutrition Program for Women, Infants and Children (WIC) serves 53% of all infants born in the United States. Our breastfeeding expert, Dr. Spatz, explains some of the aspects of the program that are not widely known.